2011
DOI: 10.1111/j.1469-0691.2010.03287.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human herpesvirus 8 and hepatitis C virus in a rural community with a high risk for blood-borne infections in central China

Abstract: Former illegal blood donation in the past decade has caused HIV outbreaks in some rural areas in China. Other HIV associated virus infections, such as human herpesvirus 8 (HHV8) in such areas are still not well defined. In order to explore HHV8 and HCV seroprevalence and potential risk factors in such areas, a cross-sectional study with 305 HIV positive and 315 HIV negative subjects recruited from a rural county in Shanxi province was conducted, where illegal blood collection was reported. Interview questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 28 publications
3
13
0
Order By: Relevance
“…Consistent with a previous report, the ethnic disparities in KSHV infection in Xinjiang was detected in our study as well. Han people were less likely to be infected by KSHV, though the prevalence of KSHV in Xinjiang Han Chinese was significantly higher than their counterparts in other provinces . We speculate the ethnic disparity in KSHV infection might not only ascribe to the disparate genetic background, but the different culture background and religious belief, and the resulting distinct behaviors, such as diet and sexual contact.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Consistent with a previous report, the ethnic disparities in KSHV infection in Xinjiang was detected in our study as well. Han people were less likely to be infected by KSHV, though the prevalence of KSHV in Xinjiang Han Chinese was significantly higher than their counterparts in other provinces . We speculate the ethnic disparity in KSHV infection might not only ascribe to the disparate genetic background, but the different culture background and religious belief, and the resulting distinct behaviors, such as diet and sexual contact.…”
Section: Discussionmentioning
confidence: 88%
“…In most provinces of China, the seroprevalence of KSHV is less than 11% in the general population . However, Xinjiang Uygur autonomous region, located in northwestern China and diverse in ethnicity, has a significantly higher incidence of KS and a higher seroprevalence of KSHV .…”
Section: Introductionmentioning
confidence: 99%
“…Seminal shedding of HHV-8 has been reported more frequently in MSM [4042], but a limitation is that we did not evaluate oral shedding [4346], and this should be pursued given these results. With the historical connections between Kaposi sarcoma and the male-to-male sex for HIV-1 and HHV-8 infections, the associations between HIV-1 and HHV-8 genital tract shedding should be explored further, and might be especially important among African populations where HHV-8 and Kaposi sarcoma prevalence is higher [4749]. …”
Section: Discussionmentioning
confidence: 99%
“…As previously described (17), study participants were patients confirmed to be infected with HIV who had been registered with the National HIV/AIDS Information System and who were participating in an ongoing HIV cohort study that was established in 2006 in the City of Yuncheng, Shanxi Province in Central China. This site is where the HIV epidemic was first reported in 1996 and HIV was predominantly transmitted through plasma/blood donation or transfusion.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the current study specifically examined antibody seropositivities to lytic and latent HHV8 antigens among a sample of previously reported patients infected with HIV (17). Knowledge gained from this study should help to better understand host immune responses to HHV8 infection in the context of HIV infection and viral coinfections.…”
Section: Introductionmentioning
confidence: 99%